0
$\begingroup$

For two operators, $A(t)$ and $B(t)$ the retarded Green’s function is defined as \begin{equation} G^R(t,t') \equiv \langle \langle A(t)|B(t) \rangle \rangle^R = -i\theta(t-t')\langle \{A(t),B(t')\} \rangle \end{equation}

then one can show that \begin{align*} i\dfrac{\partial}{\partial t} G^R(t,t') & = \delta(t-t')\langle \{A(t),B(t')\} \rangle - i \theta(t-t')\langle \{i\dfrac{\partial A(t)}{\partial t},B(t')\} \rangle \\ & = \delta(t-t')\langle \{A(t),B(t')\} \rangle - i \theta(t-t')\langle \{[A(t),H(t)],B(t')\} \rangle \\ & = \delta(t-t')\langle \{A(t),B(t')\} \rangle + \langle \langle [A(t),H(t)]|B(t') \rangle \rangle^R \end{align*} If the Hamiltonian $H$ in Schrodinger picture is independent of time, then the correlation functions depend on $(t-t')$, not on $t$ and $t'$ separately. We can go to the Fourier space,the EOM becomes \begin{equation} \boxed{\omega \langle \langle A|B \rangle\rangle^R = \langle \{A,B\} \rangle + \langle \langle [A,H]|B \rangle\rangle^R}. \end{equation}

Starting with this formula, I want to derive the analytical expression for retarded Green's function with the following Hamiltonian $H$ (fermionic system): \begin{equation} H = \sum_k x a_k^\dagger a_k + \sum_{m \neq n} y (a^\dagger_m a_n + a^\dagger_n a_m) \end{equation}

This following is my solution: \begin{equation} \boxed{A=a_s,B=a^\dagger_t} \Rightarrow \omega \langle \langle a_s|a^\dagger_t \rangle \rangle^R = \langle \{a_s,a^\dagger_t\} \rangle + \langle \langle [a_s,H]|a^\dagger_t \rangle \rangle^R \end{equation}

\begin{align*} [a_s,H] & =\left[a_s,\sum_k x a_k^\dagger a_k + \sum_{m \neq n} y (a^\dagger_m a_n + a^\dagger_n a_m) \right ]\\ & = \sum_k x \{a_s,a_k^\dagger\}a_k + \sum_{m \neq n} y \{a_s,a_m^\dagger\}a_n +\sum_{m \neq n} y \{a_s,a_n^\dagger\}a_m \\ & = x a_s+ \sum_{n} y a_n \qquad (s=m \neq n) \end{align*}

\begin{equation} \omega G_{st}^R = \delta_{st} + x G_{st}^R + \sum_n y \langle \langle a_n|a^\dagger_t \rangle \rangle^R \Rightarrow G_{st}^R = \dfrac{\delta_{st}+y\sum_n G^R_{nt}}{\omega-x} \end{equation}

But this result is the final solution? Or how can I further simplify my results?

$\endgroup$
0
$\begingroup$

$\textbf{Quick hint:}$ Using this answer. You just have to identify a specific form of $\mathbb{H}=\left(x-y\right)\mathbb{I}_{N \times N}^{}+ y \mathbb{J}_{N \times N}^{}$, with $\mathbb{I}_{N \times N}^{}$ and $\mathbb{J}_{N \times N}^{}$ being identity matrix and matrix of ones respectively. $\mathbb{G}_{}^{R}(E)=\left[E\mathbb{I}-\mathbb{H}+i 0_{}^{+}\mathbb{I}\right]_{}^{-1}$ can be found analytically using Sherman-Morrison formula.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.